2012
DOI: 10.1371/journal.pone.0044389
|View full text |Cite
|
Sign up to set email alerts
|

Protein Disorder and Short Conserved Motifs in Disordered Regions Are Enriched near the Cytoplasmic Side of Single-Pass Transmembrane Proteins

Abstract: Intracellular juxtamembrane regions of transmembrane proteins play pivotal roles in cell signalling, mediated by protein-protein interactions. Disordered protein regions, and short conserved motifs within them, are emerging as key determinants of many such interactions. Here, we investigated whether disorder and conserved motifs are enriched in the juxtamembrane area of human single-pass transmembrane proteins. Conserved motifs were defined as short disordered regions that were much more conserved than the adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Determination of structures of receptor cytoplasmic tails is difficult as they are usually small, have several disordered regions, and are subject to post translational modifications and conformational changes upon ligand binding 46 . HXMS can be extremely useful in determining folded and unfolded regions of cytoplasmic tails of receptors.…”
Section: 1 Identification Of Disordered Regions In Proteins By Hxmsmentioning
confidence: 99%
“…Determination of structures of receptor cytoplasmic tails is difficult as they are usually small, have several disordered regions, and are subject to post translational modifications and conformational changes upon ligand binding 46 . HXMS can be extremely useful in determining folded and unfolded regions of cytoplasmic tails of receptors.…”
Section: 1 Identification Of Disordered Regions In Proteins By Hxmsmentioning
confidence: 99%
“… 6 - 12 In a previous in silico analysis we showed that disordered regions tend to reside in the juxtamembrane region of transmembrane proteins potentially accommodating linear motifs. 13 A family of transmembrane proteins, cadherins, was predicted to contain potential bioactive regions close to the membrane at their cytoplasmic side. Cadherins mediate Ca 2+ -dependent, homophillic, cell-cell interactions, called adherens junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Dozens of pieces of evidence are required to confirm the functionality of a linear motif, as the information content of the peptide is very low and most of their occurrence in proteins are just 'random' false positive hits. There are several other efforts for the large scale computational identification and analysis of putative linear motifs in membrane proteins [35]. Here we demonstrated that such considerations have a strong predictive power, even if a significant proportion of the identified motifs is likely not functional.…”
Section: Limitation Of Our Methodsmentioning
confidence: 57%